The Effect of Moringa Leaf Supplementation on Lemongrass Waste-Based Rations on Crude Fiber, Crude Fat, and Nitrogen-free Extract: Evaluasi kandungan Serat Kasar, Lemak Kasar, dan BETN pada Ransum Berbasis Limbah Serai Wangi yang disuplementasi ekstrak Daun Kelor sebagai Antioksidan - Astuti, Tri; Alfajar, safitri; Akbar, Syahro Ali; Basyirun, Fajri; Surtina, Dara (Buletin Peternakan Tropis, 2024)
This research was conducted to determine the effect of moringa leaf extract supplementation as a source of natural antioxidants in a complete ration based on fermented citronella oil distillation by-products on the content of crude fiber, crude fat, and nitrogen-free extract. This research used a Completely Randomized Design, five treatments, and three replications for each treatment. The treatments consisted of antioxidant supplementation with doses: of 0% (P0/control), 0.125% (P1), 0.25% (P2), 0.375% (P3), and 0.50% (P4). The variables measured included crude fiber, crude fat, and NFE content. The results of the study showed that the lowest average crude fiber content was in treatment P3 (25.43%), the lowest crude fat content was in P4 (1.88%), and the highest NFE content was in P4 (47.83%). Supplementation of moringa leaf antioxidants in fermented lemongrass waste-based rations with various doses (0%, 0.125%, 0.25%, 0.375%, 0.50%) showed no significant effect (P>0.05) on crude fiber, crude fat, and BETN content. The research concludes that supplementation of moringa leaf extract as a source of natural antioxidants showed no significant effect on crude fiber, crude fat, and NFE content